Male Postpartum Depression: A Neglected Issue in Pakistan - Shaharyar Usman; Abhishek Lal (Pakistan Journal of Medicine and Dentistry)
The birth of a child is considered one of the most joyous occasions for new parents along with their entire family and relatives. However, there are times when new fathers during this occasion face an important issue that is often neglected, called Male Postpartum Depression (PPD) 1. During the initial months, new mothers may experience maternal PPD, hence support and treatments are offered to such individuals. 1. In comparison to maternal PPD, male PPD is not well documented and is often neglected. Male PPD presents differently than female PPD whereby they may experience irritability, anxiety, lack of interest in activities that were previously considered enjoyable, social withdrawal, along changes in sleeping and eating patterns. 1.